Characteristics Associated with Acute-Phase Response following First Zoledronic Acid Infusion in Brazilian Population with Osteoporosis - Bruno S. A. Ferreira; Bernardo M. da Cunha; Luciana P. Valadares; Larissa A. Moreira; Frederico G. A. Batista; Cristiane da F. Hottz; Marina M. P. Lins; Gabriel G. R. Magalhães; Luanna M. de Arruda; Sergio H. R. Ramalho (Journal of Osteoporosis)
We aimed to evaluate characteristics associated with acute-phase response (APR) following first zoledronic acid infusion in a Brazilian cohort. This retrospective cohort study enrolled all adults with osteoporosis who underwent a first zoledronic acid infusion at our centre between June 2015 and June 2019. Clinical demographics (age, sex, diabetes, smoking, body mass index, and previous oral bisphosphonate use) and laboratory data (calcium, parathyroid hormone, renal function, and serum 25-hydroxyvitamin D and carboxy-terminal crosslinked telopeptide of type 1 collagen [CTX], both before and after infusion) were compared between patients with and without APR. We evaluated association magnitude between the presence of APR and clinical variables through logistic regression. This study enrolled 400 patients (women, 80%). APR was observed in 24.5% (n = 98) of patients. The mean symptom duration in days was 3.5 ± 2.8. Patients with APR were younger (67 ± 12 vs. 71 ± 11 years; p=0.001), used oral bisphosphonates less frequently (34% × 50%; p=0.005), and had greater baseline CTX (0.535 ng/mL [0.375, 0.697] × 0.430 [0.249, 0.681]; p=0.03) and ΔCTX (−69 [−76; −50] × −54 [−72; −23]; p=0.002) than those without APR. The other variables were similar between the groups. Only ΔCTX was associated (OR, 0.62; 95% CI 0.41–0.98) with APR after accounting for age and bisphosphonate use. APR occurred in 24.5% of the cohort. Younger age and absence of prior oral bisphosphonate use were associated with APR following first zoledronic acid infusion. APR was associated with ΔCTX (but no other variables) after adjusting for these factors.